Cross-Modal Transfer Following Auditory Task-Switching Training in Old Adults - Toovey, Benjamin Robert William; Kattner, Florian; Schubert, Torsten (Frontiers in Psychology, 2021)
Maintaining and coordinating multiple task-sets is difficult and leads to costs, however task-switching training can reduce these deficits. A recent study in young adults (Kattner et al., 2019) demonstrated that this training effect occurs at an amodal processing level. Old age is associated with reduced cognitive plasticity and further increases the performance costs when mixing multiple tasks. Thus, cognitive aging might be a limiting factor for inducing cross-modal training effects in a task-switching environment. We trained participants, aged 62-83 years, with an auditory task-switching paradigm over four sessions (2880 total trials), to investigate whether training-related reductions in task-switching costs would also manifest in an untrained visual modality version of the task. Two control groups trained with single tasks (active control) or not trained (passive control) allowed us to identify improvements specific to task-switching training. To make statistical evaluations of any age differences in training and cross-modal transfer, the data from the Kattner cohort were incorporated into the present analysis. Despite the tendency for older adults to respond more cautiously, task-switching training specifically led to a mixing cost reduction in both trained and untrained modalities, the magnitude of which was statistically similar regardless of age. In line with a growing body of research, we failed to observe any far transfer effects in measures of inhibition, working memory or fluid intelligence. Overall, we conclude that any apparent cognitive limitations associated with aging do not prevent cognitive control processes which support set-shifting from improving at an amodal level.